Improving Science Learning Outcomes Through the STAD Type Cooperative Learning Model at SD Negeri 008 Rambah Hilir - Jandriadi, Jandriadi (STKIP Rokania Pasir Pangaraian, 2023)
, The learning pattern carried out in science lessons in class V so far, only relies on one type of conventional method, namely the lecture method and rarely uses teaching aids as a learning medium. So students are less motivated in learning which results in maximum learning achievement results being difficult to achieve. So it is necessary to improve learning, namely by implementing the Student Teams Achievement Division (STAD) learning model and using teaching aids. The subjects of this research were all fifth grade students at SDN 008 Rambah Hilir for the 2021 - 2022 academic year with a total of 21 students consisting of 13 male students and 8 female students. Broadly speaking, there are four stages that are followed in carrying out classroom action research, namely: planning, implementation, observation, and reflection. The research results showed that the classical learning completeness value (KB) in pre-cycle learning was 57%, whereas in the first cycle it was 71% and in the second cycle the learning completeness value was 100%, which means that classical learning has achieved learning completeness. In this way, student learning outcomes on the subject of adapting living creatures to their environment can be improved through the STAD Type Learning Model and the use of teaching aids.